2012
DOI: 10.1002/ana.23764
|View full text |Cite
|
Sign up to set email alerts
|

Mild passive focal cooling prevents epileptic seizures after head injury in rats

Abstract: Objective Posttraumatic epilepsy is prevalent, often difficult to manage, and currently cannot be prevented. While cooling is broadly neuroprotective, cooling-induced prevention of chronic spontaneous recurrent seizures has never been demonstrated. We examined the effect of mild passive focal cooling of the perilesional neocortex on the development of neocortical epileptic seizures after head injury in the rat. Methods Rostral parasagittal fluid percussion injury in rats reliably induces a perilesional, neoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 47 publications
2
47
1
Order By: Relevance
“…Our previous work has shown that, while rpFPI is progressive in seizure frequency and duration, behavioral correlates, and underlying pathology, the frequency of focal neocortical seizures originating from the perilesional epileptic focus appears relatively stable for a period of several weeks around 1 month post-injury (Curia et al, 2011; D’Ambrosio et al, 2005, 2013). This is, thus, a convenient time for the assessment of investigational treatments, and we have successfully used periodic recordings to evaluate both AS and AEG/DM effects on frontal neocortical PTE at 1 month postinjury (D’Ambrosio et al, 2013; Eastman et al, 2010, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous work has shown that, while rpFPI is progressive in seizure frequency and duration, behavioral correlates, and underlying pathology, the frequency of focal neocortical seizures originating from the perilesional epileptic focus appears relatively stable for a period of several weeks around 1 month post-injury (Curia et al, 2011; D’Ambrosio et al, 2005, 2013). This is, thus, a convenient time for the assessment of investigational treatments, and we have successfully used periodic recordings to evaluate both AS and AEG/DM effects on frontal neocortical PTE at 1 month postinjury (D’Ambrosio et al, 2013; Eastman et al, 2010, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This is, thus, a convenient time for the assessment of investigational treatments, and we have successfully used periodic recordings to evaluate both AS and AEG/DM effects on frontal neocortical PTE at 1 month postinjury (D’Ambrosio et al, 2013; Eastman et al, 2010, 2011). In the present study, continuous ECoG recordings conducted 1 month postinjury detected numerous CSRSs with focal perilesional onset that did (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This resulted in the FDA never approving carisbamate for partial-onset seizures, despite the preclinical efficacy in relevant animal models (Bialer et al, 2009). There is now a concerted effort to develop and implement new preclinical models of epilepsy (Barton et al, 2001;Bouilleret et al, 1999;D'Ambrosio et al, 2013;Stewart et al, 2010) in an attempt to overcome the perceived similarity in efficacy of many antiseizure drugs. These new models may be useful in the identification, differentiation, and development of compounds with novel mechanisms of action, attempting not only to confer an improved antiseizure effect (particularly in the patients who have been resistant to all available therapies), but ideally to modify the course of the underlying disease (disease modification and perhaps even antiepileptogenesis; Kelley et al, 2009;Lowenstein, 2011).…”
Section: Disease Preventionmentioning
confidence: 99%